An Evaluation Of Possible Alteration In International Policy After COVID-19 - Ağır, Osman (Fırat University, 2021)
COVID-19, which emerged in Wuhan (China) in 2019 and spread all over the world in a very short time, has started to a multidimensional threat to humanity. The epidemic had multiple negative effects on the international system, nation-state structures, economic structures and social life in a short time. The insufficiency of the international system, which consists of the interactions between states, international organizations, regional systems and structural determinants that they have contributed to, to produce an overall solution, has caused international organizations such as the UN and the EU to experience a legitimacy crisis. Therefore, it has become debatable that international policy actors can be restructured after the epidemic. Since the beginning of the epidemic, the international community has not been able to form a concrete global strategy to combat the global pandemic. In the study, an answer to the question "What kind of changes will occur in the international system after the pandemic" will be sought. In the artıcle, the main purpose of which is to discuss possible changes that may occur in international policy after the epidemic, the political, economic and social effects of the epidemic were evaluated and possible changes in international policy after the epidemic were made.

Çin’in Wuhan kentinde 2019 yılında ortaya çıkan ve çok kısa süre içerisinde tüm dünyaya yayılan COVID-19, insanlık için çok boyutlu tehdit oluşturmaya başlamıştır. Salgının uluslararası sisteme, ulus devlet yapılanmalarına, ekonomik yapılanmalara ve toplumsal yaşama kısa sürede çok boyutlu olumsuz etkileri olmuştur. Devletler, uluslararası örgütler, bunların oluşmasına katkı sağladığı bölgesel sistemler ve yapısal belirleyiciler arasındaki etkileşimlerden oluşan uluslararası sistemin topyekün bir çözüm üretilmesi noktasında yetersiz kalması, BM ve AB gibi uluslararası oluşumların meşruiyet krizi yaşamalarına neden olmuş, salgın sonrası uluslararası politika aktörlerinin yeniden yapılandırılması tartışılır hale gelmiştir. “Pandemi sonrası uluslararası sistemde ne gibi değişimlerin yaşanacağı” sorunsalına cevap aranacak olan bu çalışmada, salgın sonrası uluslararası politikada meydana gelebilecek olası değişimlerin tartışılması amaçlanmış, salgının siyasi ekonomik ve toplumsal etkileri ele alınarak salgın sonrası uluslararası politikada meydana gelebilecek olası değişimlere yönelik değerlendirmelerde bulunulmuştur
COVİD-19 SONRASI ULUSLARARASI POLİTİKADAKİ OLASI DEĞİŞİMLERE YÖNELİK BİR DEĞERLENDİRME